A new perspective of the Alboran Upwelling System reconstruction during the Marine Isotope Stage 11: A high-resolution coccolithophore record. (1st October 2020) - González-Lanchas, Alba; Flores, José-Abel; Sierro, Francisco J.; Bárcena, María Ángeles; Rigual-Hernández, Andrés S.; Oliveira, Dulce; Azibeiro, Lucía A.; Marino, Maria; Maiorano, Patrizia; Cortina, Aleix; Cacho, Isabel; Grimalt, Joan O.
Abstract: A high-resolution study of the MIS 12/MIS 11 transition and the MIS 11 (430–376 kyr) coccolithophore assemblages at Ocean Drilling Program Site 977 was conducted to reconstruct the palaeoceanographic and climatic changes in the Alboran Sea from the variability in surface water conditions. The nannofossil record was integrated with the planktonic oxygen and carbon stable isotopes, as well as the U k ' 37 Sea Surface Temperature (SST) at the studied site during the investigated interval. The coccolithophore primary productivity, reconstructed from the PPP (primary productivity proxy = absolute values of Gephyrocapsa caribbeanica  + small Gephyrocapsa group) revealed pronounced fluctuations, that were strongly associated with variations in the intensity of the regional Alboran Upwelling System . The comparison of the nannoplankton record with opal phytolith content for the studied site and the already available pollen record at the nearby Integrated Ocean Drilling Program Site U1385, suggests an association of the upwelling dynamics with the variability of the North Atlantic Oscillation- like (NAO- like ) phase. High PPP during positive (+) NAO- like phases is the result of intensified upwelling, owing to the complete development of the surface hydrological structures at the Alboran Sea. This scenario was identified during the MIS 12/MIS 11 transition (428-422 kyr), the late MIS 11c (405-397 kyr), and MIS11 b to MIS 11a (397-376 kyr). Two short-term minima in the PPP and SST were observed during MIS 11 b and were coeval with the North Atlantic Heinrich- type (Ht) events Ht3 (∼390 kyr) and Ht2 (∼384 kyr). Increased abundance of the subpolar Coccolithus pelagicus subsp. pelagicus and Gephyrocapsa muellerae was consistent with the inflow of cold surface waters into the Mediterranean Sea during the Ht events. Lowered PPP during negative (−) NAO- like phases is the result of moderate upwelling by the incomplete development of surface hydrological structures at the Alboran Sea. This scenario is expressed during the early MIS 11c (422-405 kyr). Overall, the results of our study provide evidence of the important role of atmospheric circulation patterns in the North Atlantic region for controlling phytoplankton primary production and oceanographic circulation dynamics in the Western Mediterranean during MIS 11. Highlights: A high-resolution coccolithophore primary productivity record in the Alboran Sea reveals climate fluctuations across MIS 11. Combination of nannofossil with terrestrial proxies evidence the control of two-phase atmospherical NAO- like. A high-frequency variability in the NAO- like phases is identified during the MIS12/MIS 11 and MIS 11 substages. A comparable pattern of Heinrich- type events 3 and 2 with He of the last glacial cycle in the Alboran Sea is evidenced.